Editor's Statement - Jackson, Jr., E. Newton (My University, 2001)
The editor references September 11th and how that might impact people moving forward. He reviewed the articles in the issue and asks for new scholarship to create a legacy for the forthcoming 25 years.
Keywords: editorial